2018
DOI: 10.1055/s-0038-1675353
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI in the Identification of a Fetal Ventral Wall Defect Spectrum

Abstract: Objective  To ascertain if useful criteria for prenatal diagnosis of fetal ventral body wall defects (VBWDs) exists by reviewing published literature on diagnosis of VBWD as compared with our own diagnostic experience. Study Design  A comprehensive literature review of diagnostic criteria of fetal VBWD including pentalogy of Cantrell (POC), omphalocele, exstrophy, imperforate anus, spina bifida (OEIS), cloacal exstrophy, limb–body wall complex (LBWC), and body stalk anomaly was performed followed by a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
2
0
2
Order By: Relevance
“…Recent studies have stressed that strict classification is not as important as a thorough description and understanding of the congenital abnormalities in utero. For example, Coleman et al looked at patients with Pentalogy of Cantrell, OEIS (omphalocoele, exstrophy, imperforate anus, spina bifida), and LBWC (limb-body wall complex) as a spectrum of diseases resulting from improper closure of lateral and craniocaudal folds (5). There are many overlapping features between these three syndromes, and in their cases series, they concluded that the degree of pulmonary hypoplasia was far more indicative of prognosis than any specific classification system would have been (5).…”
Section: Defining Pentalogy Of Cantrellmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have stressed that strict classification is not as important as a thorough description and understanding of the congenital abnormalities in utero. For example, Coleman et al looked at patients with Pentalogy of Cantrell, OEIS (omphalocoele, exstrophy, imperforate anus, spina bifida), and LBWC (limb-body wall complex) as a spectrum of diseases resulting from improper closure of lateral and craniocaudal folds (5). There are many overlapping features between these three syndromes, and in their cases series, they concluded that the degree of pulmonary hypoplasia was far more indicative of prognosis than any specific classification system would have been (5).…”
Section: Defining Pentalogy Of Cantrellmentioning
confidence: 99%
“…For example, Coleman et al looked at patients with Pentalogy of Cantrell, OEIS (omphalocoele, exstrophy, imperforate anus, spina bifida), and LBWC (limb-body wall complex) as a spectrum of diseases resulting from improper closure of lateral and craniocaudal folds (5). There are many overlapping features between these three syndromes, and in their cases series, they concluded that the degree of pulmonary hypoplasia was far more indicative of prognosis than any specific classification system would have been (5). In counseling families and planning for delivery and early management, a descriptive diagnosis is more valuable than trying to line characteristics up with a specific syndrome.…”
Section: Defining Pentalogy Of Cantrellmentioning
confidence: 99%
“…Estos defectos se clasifican, de forma práctica, como periumbilicales (onfalocele y gastrosquisis), de la línea media inferior (extrofia de vejiga y extrofia de cloaca) y de la línea media superior (pentalogía de Cantrell) 7 . Otras malformaciones menos frecuentes de la pared abdominal anterior son la hernia epigástrica congénita, la displasia de pared corporal, el síndrome de Prune Belly o síndrome de vientre en ciruela pasa, la hendidura epigástrica, los defectos de pared asociados al síndrome de bridas amnióticas (síndrome de cordón corto) [8][9][10][11] .…”
Section: Discussionunclassified
“…La única forma de detectar oportunamente esta anomalía es por medio de ultrasonografía y debe considerarse esta patología ante un defecto severo de la pared abdominal 3 . Además, en la mayoría de los casos se observa un aumento de la translucencia nucal y la elevación de la alfafetoproteína 3 , de ahí la importancia de seguir adecuadamente el protocolo de ultrasonografías durante el control prenatal [6][7][8][9][10][11] , donde la primera se indica de las 11 a las 13 semanas 6 días, la segunda de las 18 a las 24 semanas y la última en el final del tercer trimestre 6 .…”
Section: Acceso Abiertounclassified
“…Fetal MRI has an important role in the diagnosis of fetal ventral body wall defects like omphalocele, exstrophy, cloacal exstrophy, pentalogy of Cantrell (POC), etc. 17,18 In the study conducted by Victoria et al, they concluded that fetal MRI is an important tool to diagnose abdominal wall defects. 19 In their study, they elaborated on abdominal wall defects ranging from the mild umbilical cord hernia to the highly complex limb-body wall syndrome.…”
Section: A C Bmentioning
confidence: 99%